Ripretinib inhibits HIV-1 transcription through modulation of PI3K-AKT-mTOR - Cai Jin-feng; Zhou Jia-sheng; Meng Zhuo-yue; Wu Zi-qi; Zhao Jia-cong; Peng Hai-xiang; Liang Xin-yu; Chen Jun-jian; Wang Pei-pei; Deng Kai (Acta Pharmacologica Sinica, 2024)
Despite the effectiveness of antiretroviral therapy (ART) in prolonging the lifespan of individuals infected with HIV-1, it does not offer a cure for acquired immunodeficiency syndrome (AIDS). The “block and lock” approach aims to maintain the provirus in a state of extended transcriptional arrest. By employing the “block and lock” strategy, researchers endeavor to impede disease progression by preventing viral rebound for an extended duration following patient stops receiving ART. The crux of this strategy lies in the utilization of latency-promoting agents (LPAs) that are suitable for impeding HIV-1 provirus transcription. However, previously documented LPAs exhibited limited efficacy in primary cells or samples obtained from patients, underscoring the significance of identifying novel LPAs that yield substantial outcomes. In this study, we performed high-throughput screening of FDA-approved compound library in the J-Lat A2 cell line to discover more efficacious LPAs. We discovered ripretinib being an LPA candidate, which was validated and observed to hinder proviral activation in cell models harboring latent infections, as well as CD4+ T cells derived from infected patients. We demonstrated that ripretinib effectively impeded proviral activation through inhibition of the PI3K-AKT-mTOR signaling pathway in the HIV-1 latent cells, thereby suppressing the opening states of cellular chromatin. The results of this research offer a promising drug candidate for the implementation of the “block and lock” strategy in the pursuit of an HIV-1 cure.